Impact of Iron oxide nanoparticles on sustainable production of biogas through anaerobic co-digestion of chicken waste and wastewater - Al Bkoor Alrawashdeh, Khalideh; Al-Zboon, Kamel K.; Rabadi, Said Al; Gul, Eid; AL-Samrraie, La’aly A.; Ali, Rabia; Al-Tabbal, Jalal A. (Frontiers in Chemical Engineering, 2022)
As The effect of iron oxide nanoparticles (IONPs) on the anaerobic co-digestion (AD) of olive mill wastewater and chicken manure was investigated. In mesophilic conditions, biogas yield, methane (CH4) content, the removal efficiency of TS, VS, acidification and hydrolysis percentage, and contaminant removal efficiency were investigated. Supplementing AD with IONPs at a concentration of 20 mg/g VS > IONPs and INOPs > 30 mg/g VS causes an inhibitor impact on biogas, methane generation, and hydrolysis. Furthermore, implantation with 20 to 30 mg of IONPs/kg VS has induced an equivalent favorable impact, with hydrolysis percentages reaching roughly 7.2 to 15.1% compared to the control test, in addition to a 1.3-4.2% enhancement in methane generation yield. The maximum acidification concentration after five days of the incubation of 1084, 9463, and 760 g/L was attained with IONPs dosages of 25, 30, and 20 mg/g VS, respectively, compared to 713 g/L obtained with the control test. The results have illustrated that supplementing AD with a specific concentration of IONPs (20 – 30 mg/g VS) has a significant effect and enhances the inhibitor removal efficiency, most possibly due to the small surface area of IONP particles. The resultant increase in the active surface area enhances the enzyme diffusion within the substrate. This study provides new data specifying the enhancement of iron oxide nanoparticles (IONPs) and identifies the impact of IONP doses at various concentrations on the AD of olive mill wastewater and chicken waste.